Stabilité des pentes par méthodes d'équilibre limite et la méthode des éléments finis : étude comparative - Bouafia, Baba; Aouissi, Aissa; Mouattah, Kaddour, Directeur de thèse (My University, 2017)
The study of slope stability is of great importance because of both human and socio-economic damage caused by the loss of stability. In this work, we have reviewed the different methods for calculating the minimum factor of safety, on the basis of which the stability of the slopes can be assesed. The purpose of this work is to carry out a comparative study between the classical methods of calculating the factor of safety and the finite element method and this by studying three different examples. At the end of this comparative study, we can conclude that the finite element method, which gives the lowest value of the factor of safety, is the one which is, a priori, the most reliable because of its speed and the absence of assumptions limiting its validity
Laghouat : Université Amar Telidji - Département de génie civil Option : Conception et calcul des structures